The role of culture: a successful knowledge creation (KC) and knowledge sharing (KS) within higher education institutions - Fakhri, Nurul Fahimah; Ahmed Mohamed, Fatima; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2015)
The higher education institution plays a crucial role as an educational organization for critical thinking for achieving academic excellence. Many good practices can be identified to support this role as a source of value creation to develop and deliver knowledge widely. The culture has a great influence to knowledge Management (KM) which operates in an institution. Knowledge creation (KC) and knowledge sharing (KS) of the university is a goal of KM by encouraging everyone recognize and participate on it as a desirable practice. KC includes the process of reproduce and create knowledge by knowledgeable people through their own and others experiences. Whereas, KS is the action of knowledge exchanged comprising information, skills, or expertise among people. Accordingly, fundamental elements of organization culture are belief, value and assumptions. These elements’ interaction describes the role of culture within an organization. This paper investigate the role of culture in the successful KC and KS within higher education institutions by examine the two world ranking university that has been mentioned in the literature review.